2011
DOI: 10.1182/blood-2011-01-329011
|View full text |Cite
|
Sign up to set email alerts
|

A novel type of congenital hypochromic anemia associated with a nonsense mutation in the STEAP3/TSAP6 gene

Abstract: STEAP3/TSAP6 encodes a ferrireductase that is involved in the acquisition of iron by developing erythroblasts and steap3/ tsap6 null-mice display severe microcytic anemia. We report a family in which 3 siblings born to healthy parents display transfusion-dependent hypochromic anemia. A nonsense STEAP3/TSAP6 was identified in the siblings at the heterozygous state. This mutation was inherited from their father while no mutation was found in their mother. A large variability of expression was found between norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…58,59 The association between a deleterious mutation and a low expressed allele has been found in several inherited disorders such as erythropoietic protoporphyria, 60 spherocytosis 61 or microcytic anemia due to STEAP3 mutations. 62 This might be a rather frequent situation since recent reports have demonstrated that preferential/specific allele expression may concern 5-20% of the genes. 63,64 Finally, hypomorphic TMPRSS6 alleles have been found to contribute to the IRIDA phenotype, despite an apparent normal biological activity in functional in vitro assay.…”
Section: Irida Phenotype With a Single Or No Mt-2 Mutation: The Case mentioning
confidence: 99%
“…58,59 The association between a deleterious mutation and a low expressed allele has been found in several inherited disorders such as erythropoietic protoporphyria, 60 spherocytosis 61 or microcytic anemia due to STEAP3 mutations. 62 This might be a rather frequent situation since recent reports have demonstrated that preferential/specific allele expression may concern 5-20% of the genes. 63,64 Finally, hypomorphic TMPRSS6 alleles have been found to contribute to the IRIDA phenotype, despite an apparent normal biological activity in functional in vitro assay.…”
Section: Irida Phenotype With a Single Or No Mt-2 Mutation: The Case mentioning
confidence: 99%
“…12 Recently, a nonsense mutation in the Steap3 gene was found to be associated with a novel type of congenital hypochromic anemia. 13 Here we demonstrate that Steap3 is the only STEAP family member highly expressed in macrophages, a cell population that functions in innate immunity. The functional characteristics illustrate the crucial roles played by macrophages in both modulation of iron homeostasis and immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…It serves as the major ferric reductase of the transferrin cycle, where it reduces endosomal Fe 3Ï© to Fe 2Ï© , which is then transported across the endosomal membrane by DMT-1 (divalent metal transporter-1) (2, 8 -10). Accordingly, the Steap3 Ϫ/Ϫ mouse exhibits microcytic, hypochromic anemia (2), and a similar phenotype has been linked to low STEAP3 expression in humans (11).…”
mentioning
confidence: 96%